Real life Applications of Internet of Things - Dilip Kumar Shaw (International Journal of Information Technology and Business, 2022)
The Internet of Things is the next technological revolution after the revolution of computer and internet. IoT integrates the new technologies of computing and communication (e.g. Sensor networks, RFID, Mobile communication and IPV6 etc). The Internet of Things is an emerging topic of technical, social, and economic significance. The term Internet of Things generally refers to scenarios where network connectivity and computing capability extends to objects, sensors and everyday items not normally considered computers, allowing these devices to generate exchange and consume data with minimal human intervention. Internet connect “all people”, Internet of Things connect “all things”. Interconnection of Things or Objects or Machines, e.g., sensors, actuators, mobile phones, electronic devices, home appliances, any existing items and interact with each other via Internet